System prawa w perspektywie jego stosowania - Mikołajewicz, Jarosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
This study is dedicated to the issue of the system of law in the process of application of law. Taking into consideration the modest on the assumption size of the text, only the selected issues — directly connected with the problems in question — were discussed within the text. In particular, the issue of the features characteristics of the system conditioning its efficiency, namely completeness and consistency. Moreover, the issue of the horizontal fragmentation of the system of law treated as a set in the collective sense and exploration of the elements of the system of law treated as one of the sets in the distributive sense. This, consequently, is analysed within the context of adjudicating on determination of specific legal situations of the legal entities.
Keywords: system prawa; stosowanie prawa